The Investigation Effects of Enalapril and Losartan on The Renal Tissues of The Experimental Diabetic Rats - Doğan, Mehmet Murat; Dönder, Emir; Kuloğlu, Tuncay; Dabak, Dürrin Özlem (Fırat University, 2011)
Objective: The aim of this study was to determine the effects of Enalapril and Losartan on renal tissues of Streptozocin(STZ)-induced diabetic rats. Materials and Methods: 28 Wistar rats were used in this study. All rats were divided into 4 groups as control group (n=7), diabetic group (n=7), DM+ Enalapril (n=7) and DM+ Losartan group (n=7). 50 mg/kg STZ administered intraperitoneally to diabetic, DM+ Enalapril, DM+ Losartan groups. Five mg/kg/day Enalapril and 10 mg/kg/day Losartan were orally administered to treatment group from the begining of the diabetes. At the end of fourth week all rats were decapitated and renal tissues were removed. Tissue samples were processed by using routine paraffin techniques. Paraffin sections were stained with periodic-acid-schiff (PAS). Results: Glomerules and tubules of control group were normal. In diabetic group; narrowing in Bowman spaces of some glomeruli, mesangial matrix enlargement and tubular dilatations were determined. Additionally; loosing of brush like edges of tubular epithelial cells, falling of the cells to the lumene of tubules, thickening of tubular basement membrane and Armanni-Ebstein lesions were determined. The histologic appearance of DM+ Enalapril and DM+ Losartan groups were similar. There were narrowing in Bowman spaces, mesangial matrix enlargement and thickening of tubular basement membranes. Tubular dilatation and Armanni-Ebstein lesions were less remarkable than diabetic group. Loosing of brush like edges of tubular epithelial cells were decreased. Conclusıons: It was determined that enalapril and losartan have healing effects on the kidney tissues of STZ- induced diabetic rats.

Amaç: Bu çalışmada, streptozotosin (STZ) ile deneysel olarak diyabet oluşturulan sıçanların böbrek dokusunda, Enalapril ve Losartan'ın iyileştirici etkilerinin incelenmesi amaçlandı. Gereç ve Yöntem: Çalışmada 28 adet erişkin, Wistar cinsi sıçan kullanıldı. Deney hayvanları Kontrol grubu (n=7), diyabetik (DM) grup (n=7), DM+ Enalapril (n=7) ve DM+ Losartan (n=7) olmak üzere dört gruba ayrıldı. Diyabetik, DM+ Enalapril ve DM+ Losartan gruplarına 50 mg/kg tek doz STZ intraperitoneal olarak uygulandı. Tedavi gruplarındaki sıçanlara diyabetin başlangıcından itibaren 5 mg/kg/gün Enalapril ve 10 mg/kg/gün losartan oral olarak verildi. Deneyin 4. haftasının sonunda sıçanlar dekapite edilerek böbrek dokuları çıkartıldı. Rutin ışık mikroskobu takibi yapılarak dokular parafin bloklara gömüldü ve Periyodik Asit-Schiff (PAS) ile boyandı. Bulgular: Kontrol grubu glomerül ve tübül yapıları normal olarak izlendi. Diyabetik grupta bazı glomerüllerde Bowman mesafesinde daralma, mezangial matriks artışı ve tübüler dilatasyon saptandı. Ayrıca tübül epitellerinin fırçamsı kenarlarında ayrılma ve bozulmalar, tübül bazal membranlarında kalınlaşma, glukojenik vakuolizasyonu gösteren şeffaf görünümlü tübüller (Armanni-Ebstein lezyonları) ve tübül lümenine dökülmeler gözlendi. Çalışmada DM+ Enalapril grubu ile DM+ Losartan grubu birbirlerine benzer histolojiye sahip olup bu gruplarda glomerüllerde Bowman mesafesinde daralma ve mezangial matriks artışı izlendi. Tübüler dilatasyonlar ve Armani-Ebstein lezyonları ise diyabetik gruba göre daha az belirgindi. Tübül epitellerinin fırçamsı kenarlarındaki ayrılma ve bozulmalar daha az belirgindi. Sonuç: STZ ile deneysel olarak diyabet oluşturulan sıçanların böbrek dokusunda enalapril ve losartanın diyabetik nefropatinin histolojik bulguları üzerine etkili olduğu belirlendi.
Deneysel Diyabetin Sıçan Böbrek Dokusunda Meydana Getirdiği Değişiklikler Üzerine Enalapril ve Losartan'ın Etkilerinin İncelenmesi